A large dinuclear Fe(ii) triple helicate demonstrating a two-step spin crossover. Issue 62 (7th July 2020) - Howard-Smith, Kyle J.; Craze, Alexander R.; Zenno, Hikaru; Yagyu, Junya; Hayami, Shinya; Li, Feng
Abstract : The largest reported dinuclear Fe(ii ) triple helicate system to exhibit spin crossover is presented, with exploration of the two-step spin-transition. Abstract : Reported herein, the synthesis as well as the structural and magnetic characterisation of the largest reported dinuclear Fe(ii ) triple helicate system to exhibit spin crossover—and also a rare example of a 273° helical twist using aromatic spacers—is presented, with exploration of the two-step spin-transition observed.